Effect of novel swirl distributor plate on gasification efficiency of bubbling fluidized bed gasifier - Eslami Afrooz, I. (Springer Science and Business Media Deutschland GmbH, 2020)
Distributor plate is the most important aspect of the fluidized bed gasifier (FBG) design. Its main function is to uniformly distribute fluidized medium through the cross section of the bed and as a result, to provide a good gas-fuel mixing. Therefore, a success or failure fluidization in an FBG is strongly dependent on its distributor plate performance. To this end, a novel distributor plate called swirl distributor plate (SDP) was designed and built in order to enhance the gas-fuel mixing and heat transfer. The effect of SDP on gasification was studied experimentally. Results were compared with conventional distributor plate (CDP). Compering with conventional distributor, an enhancement in syngas production was observed, while the fluidized bed gasifier was equipped with novel SDP. Moreover, the results show 15.90 and 6.63 improvement in the values of carbon conversion and cold gas efficiency. Â© Springer Nature Singapore Pte Ltd 2020.